Manajemen Lintas Budaya - Suryanto Suryanto (The Winners, 2001)
This article explains about globalization versus national resposiveness matrix, meeting the challenge, cross cultural differences and similiarities, parochialism and simplification, also cultural differences in selected countries and regions. The purpose of the research is to find factor, method, strategy in order to bridging management across cultural, so that a manager can have a better view in making a decision based on cultural differences and need of the company. From this article can be concluded that there are four factor that must be consider in Multi National Company (MNC). Those factors are (1) It’s important to be divided in worldwide standard; (2) It’s important to differennate product at the local market; (3) It’s important to have insider; (4) there is one more contribution to local condition. In order to succeed in MNC, a company must survive from across cultural threat, there are parodialism and simplification.